2018
DOI: 10.1093/femsle/fny057
|View full text |Cite
|
Sign up to set email alerts
|

The primary biological network of Bifidobacterium in the gut

Abstract: Bacterial interactions in the biological network affect the growth of Bifidobacterium. In the present study, five habitats were constructed by changing animals, their health statuses and their diets. In each of these habitats, different networks of Bifidobacterium were outlined through correlation analysis of the 50 most dominant microbes. Thirty-eight bacterial genera directly correlated with the growth of Bifidobacterium, including 23 genera with a positive correlation and 15 genera with a negative correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…There is a study [ 24 ] which showed that the amount of prausnitzii was inversely associated with the activity of inflammatory bowel disease and colon cancer. Some bifidobacterium [ 25 ] strains are considered to produce beneficial bacteria to the body, less content in the intestine but have a significant impact on human health. Its multiple biological functions have been reported, such as immune regulation, antitumor activity, anti-inflammation, antiaging, antiaging, reducing blood lipid, etc.…”
Section: Discussionmentioning
confidence: 99%
“…There is a study [ 24 ] which showed that the amount of prausnitzii was inversely associated with the activity of inflammatory bowel disease and colon cancer. Some bifidobacterium [ 25 ] strains are considered to produce beneficial bacteria to the body, less content in the intestine but have a significant impact on human health. Its multiple biological functions have been reported, such as immune regulation, antitumor activity, anti-inflammation, antiaging, antiaging, reducing blood lipid, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Bifidobacteria, as a probiotic, plays important roles in immune regulation, anti-tumour, anti-pathogenicity and anti-inflammation, and can produce acetate to protect the enteropathogenic infection. (Fukuda et al 2011;Luo et al 2018). Cupriavidus can catabolize intestinal amino acid by secreting various enzymes (Ueatrongchit and Asano 2011).…”
Section: Discussionmentioning
confidence: 99%
“…2011; Luo et al . 2018). Cupriavidus can catabolize intestinal amino acid by secreting various enzymes (Ueatrongchit and Asano 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, Lactobacillus and Bifidobacterium , which played important roles in maintaining intestinal homeostasis and fortifying the intestinal mucus layer ( 27 , 28 ) in the present study were significantly proliferated in HF treatment. Higher abundance of cecal Lactobacillus positive regulated a better feed efficiency ( 2 ), while increased Bifidobacterium correlated with reduced adiposity and levels of microbe-derived inflammatory molecules ( 29 ).…”
Section: Discussionmentioning
confidence: 53%